2004
DOI: 10.1111/j.1365-3156.2004.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control of schistosomiasis through community participation in a Moroccan oasis

Abstract: SummaryAkka oasis, in the province of Tata, southern Morocco, is one of the oldest foci of urinary schistosomiasis in Morocco where transmission is still taking place. We report the results of two studies: a cross-sectional snail survey investigated the distribution of Bulinus truncatus in relation to habitat factors in the Akka traditional irrigation system. The presence of aquatic vegetation, especially Potamogeton sp. was identified as a key factor determining snail occurrence and abundance in canals, impou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 6 publications
5
36
1
Order By: Relevance
“…A low concentration of oxygen, even if not immediately fatal to the snail, reduces its movements and thus impairs feeding and reproduction (Malek, 1958). An increase in snail abundance influenced by an increase in dissolved oxygen observed in this study has also been reported elsewhere (Boelee & Laamrani, 2004). The higher conductivity values reported in the wet season is unusual as other reports have indicated higher levels in the dry season (Tubonimi et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A low concentration of oxygen, even if not immediately fatal to the snail, reduces its movements and thus impairs feeding and reproduction (Malek, 1958). An increase in snail abundance influenced by an increase in dissolved oxygen observed in this study has also been reported elsewhere (Boelee & Laamrani, 2004). The higher conductivity values reported in the wet season is unusual as other reports have indicated higher levels in the dry season (Tubonimi et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…has been shown to reduce at temperatures above 30 º C due to pathological changes in the reproductive system of the snails (Madsen, 1985).High temperature causes thermal stress in snail vectors and shows an inverse relationship with dissolved oxygen (Hofkins et al, 1991).The temperature range of 21.7 -29 °C recorded in all river bodies during the study appears therefore to be favourable to the aquatic snails, as there were no significant changes in temperature throughout the sampling seasons. The mean pH value in all the water bodies in the present study was within favourable limits for aquatic snail development (Boelee & Laamrani, 2004). The higher mean pH value recorded during the dry season could be due to higher transparency of the water bodies resulting in active removal of carbon (iv) oxide and consequently production of oxygen through photosynthesis.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, more systematic planning could help to prevent the negative health impacts of water storage and enhance the benefits for increased resilience against climate change. In Morocco (Boelee and Laamrani 2004) and Ethiopia (Yohannes et al 2005), participatory approaches led to increased awareness and community action for environmental disease control around water impoundments. In many parts of the world, particularly in subSaharan Africa, capacity for HIA is limited and working in a participatory way with interdisciplinary teams and local users remains uncommon.…”
Section: Ethiopiamentioning
confidence: 99%
“…Chenq (1971) reported that in Kiagsu and Chekiang provinces of China, the 10.5 million cases of schistosomiasis estimated to be present by 1955 were claimed to have been reduced by one third using ecological procedures in combination with the storage of night soil before use on the land and a three day treatment campaign with tartar emetic. The reduction in the water level, including complete drainage of the habitat, resulted in the death of the snails through desiccation (Boelee & Laamrani, 2004). Similarly, the ecological benefits to the snails such as, the presence of algae which served as their main source of food are removed.…”
Section: Ecological Modificationmentioning
confidence: 99%
“…Local participation is known to ensure the sustainability of this approach. In Morocco, the cost of control was reduced while the people took responsibility for their environment and health (Boelee & Laamrani, 2004). Strickland (1982) noted that such environmental management led to improved agricultural productivity in endemic areas.…”
Section: Ecological Modificationmentioning
confidence: 99%